Tobacco Products, Periodontal Health and Education Level: Cohort Study from Sweden - Anna Julkunen-Iivari; Anna Maria Heikkinen; Ismo T. Räisänen; Hellevi Ruokonen; Jukka H. Meurman; Sanna Toppila-Salmi; Per-Östen Söder; Birgitta Söder (Dentistry Journal, 2020)
Background: The aim of this study is to investigate if using tobacco products (including snuff, smoking tobacco and dual-using) associates with periodontal health, education level and mortality in a Swedish cohort, hypothesizing that tobacco products affect periodontal health, associate with lower education and increase the risk of death. Method: Study cohort of 1080 subjects aged 31–40 years (528 men, 552 women) was clinically examined and interviewed in 1985 and followed for mortality until 2015. Subjects were classified into two groups: “tobacco users” and “non-users”. Associations between periodontal health parameters, tobacco products, education level and age of death were analysed. SPSS was used for analyses. Results: Tobacco products, as well as education level associated, with poor periodontal health. Tobacco users and lower education was linked to higher plaque-, calculus- and gingival-index scores than non-users (p < 0.001). They also had significantly higher prevalence of deep periodontal pockets (≥5 mm) (p < 0.001 and 0.010, respectively), missing teeth (p = 0.010 and 0.003, respectively) and lower education level (p < 0.001) compared with non-users. However, tobacco product users did not die significantly earlier than non-users. Conclusion: Tobacco products had a negative impact on periodontal health. Tobacco product users were less educated. However, using tobacco products may not cause premature death.